DIVERSITY OF SNAKE RESCUED FROM RESIDENTIAL AREAS IN GREATER JAKARTA METROPOLITAN AREA, INDONESIA - Ira Khoerunisa; Mirza Dikari Kusrini; Ani Mardiasturi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2021)
Development and habitat loss in Greater Jakarta Metropolitan Area affected snakes and forced them to adapt in urban areas. Snakes in residential areas might increase encounter rate with humans which lead to human-snake conflict. The objectives of this research were to identify the diversity of snakes in residential areas based on rescue effort and to documents effort of those organizations on how to mitigate human-snake conflict through snake relocation. From 2015-2019, 37 snake species were reported found around residential areas in Jakarta Metropolitan Area. Javan spitting cobra Naja sputatrix and reticulated python Malayopython reticulatus are the most encountered snakes in residential areas. Jakarta has the highest total encounter of snakes compared to other area but Bogor has the highest diversity of snake species. Snake found in residential areas are sometimes “rescued” by snake reptile enthusiasts who formed a group. Most of these group does not have standard operating procedure when rescuing snake. Human-snake conflict can be mitigated by relocation of snakes, education, and translocation, although the impact of translocation should be evaluated further. Key words: Jakarta Metropolitan Area, human-snake conflict, Urban area, snake rescue